Language Power in Virtual Market: Analyzing Illocutionary Functions of Marketplaces’ Slogan in Indonesia - Ponia Mega Septiana; Wiwi Widuri Sinta Putri Sari; Imam Muhtadi (Faculty of Letters Universitas Balikpapan, 2023)
This research aims to find the classification of the illocutionary act and illocutionary function in slogan online marketplace in Indonesia. The data are taken from the highest-ranking visitation by the customer on the website sasanadigital.com during June 2023. The main theory used is based on Yule (2010) about the illocutionary act and Leech (1993) about the illocutionary functions. The research uses a descriptive qualitative method. The result of the research shows 4 types of the illocutionary act. They are assertive, commissive, directive, and declarative and the illocutionary functions based on most classifications appear that be collaborative and competitive.